Delaunay algorithm and principal component analysis for 3D visualization of mitochondrial DNA nucleoids by Biplane FPALM/dSTORM - Alán, Lukáš; Špaček, Tomáš; Ježek, Petr (European biophysics journal, 2016)
Data segmentation and object rendering is required for localization super-resolution microscopy, fluorescent photoactivation localization microscopy (FPALM), and direct stochastic optical reconstruction microscopy (dSTORM). We developed and validated methods for segmenting objects based on Delaunay triangulation in 3D space, followed by facet culling. We applied them to visualize mitochondrial nucleoids, which confine DNA in complexes with mitochondrial (mt) transcription factor A (TFAM) and gene expression machinery proteins, such as mt single-stranded-DNA-binding protein (mtSSB). Eos2-conjugated TFAM visualized nucleoids in HepG2 cells, which was compared with dSTORM 3D-immunocytochemistry of TFAM, mtSSB, or DNA. The localized fluorophores of FPALM/dSTORM data were segmented using Delaunay triangulation into polyhedron models and by principal component analysis (PCA) into general PCA ellipsoids. The PCA ellipsoids were normalized to the smoothed volume of polyhedrons or by the net unsmoothed Delaunay volume and remodeled into rotational ellipsoids to obtain models, termed DVRE. The most frequent size of ellipsoid nucleoid model imaged via TFAM was 35 × 45 × 95 nm; or 35 × 45 × 75 nm for mtDNA cores; and 25 × 45 × 100 nm for nucleoids imaged via mtSSB. Nucleoids encompassed different point density and wide size ranges, speculatively due to different activity stemming from different TFAM/mtDNA stoichiometry/density. Considering twofold lower axial vs. lateral resolution, only bulky DVRE models with an aspect ratio >3 and tilted toward the xy-plane were considered as two proximal nucleoids, suspicious occurring after division following mtDNA replication. The existence of proximal nucleoids in mtDNA-dSTORM 3D images of mtDNA "doubling"-supported possible direct observations of mt nucleoid division after mtDNA replication.
Keywords: DNA vazebné proteiny; analýza hlavních komponent; Nucleic Acid Conformation; DNA, Mitochondrial; lidé; buňky Hep G2; Hep G2 Cells; Humans; Principal Component Analysis; fluorescenční mikroskopie; algoritmy; DNA-Binding Proteins; Algorithms; konformace nukleové kyseliny; mitochondriální proteiny; mitochondriální DNA; Microscopy, Fluorescence; zobrazování trojrozměrné; Imaging, Three-Dimensional; molekulární modely; Models, Molecular; Mitochondrial Proteins